The Title Should Use As Few Words As Possible While Accurately Describing The Content Of The Article - Agnes Gading Putri Afifah; Nelly Marhayati; Bakhrul Ulum (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aims to analyze the effectiveness of the edutainment method in improving early childhood children's Qur'an memorization ability at TK IT Al Kiswah Bengkulu City. This research was motivated by the low ability of children to memorize the Qur'an, which was indicated by low concentration, low learning motivation, and the use of monotonous learning methods. This study employed a quantitative approach with a quasi-experimental design using a Nonequivalent Control Group Design. The research subjects consisted of 42 children in Group B, comprising 21 children in the experimental group and 21 children in the control group. Data were collected through observation, tests, and documentation. Data analysis was conducted using SPSS version 26 through normality tests, homogeneity tests, and hypothesis testing using the Independent Sample T-Test. The results showed that the experimental group's pretest mean score was 48.76, while the control group's was 47.89. After the treatment, the experimental group's posttest mean score increased to 87.14, whereas the control group's score increased to 72.95. The hypothesis test yielded a significance value of 0.000 < 0.05, indicating a significant difference between the experimental and control groups. Therefore, the edutainment method was proven effective in improving early childhood children's Qur'an memorization ability at TK IT Al Kiswah Bengkulu City. The edutainment method was able to create a fun learning atmosphere and improve children's concentration, motivation, active participation, and memory during the learning process.